A New Geldanamycin Analogue from Streptomyces hygroscopicus - Hao Zhang; Guang-Zhi Sun; Xiang Li; Hong-Yu Pan; Yan-Sheng Zhang (Molecules, 2010)
A new geldanamycin analogue was isolated from Streptomyces hygroscopicus A070101. The structure was elucidated as 11-methoxy-17-formyl-17-demethoxy-18-O-21-O-dihydrogeldanamycin (1) on the basis of extensive 1D and 2D NMR as well as HRESI-MS spectroscopic data analysis. Compound 1 showed considerable cytotoxicity (SRB) against human cancer cell lines (breast cancer MCF-7, skin melanoma SK-MEL-2 and lung carcinoma COR-L23).